2015
DOI: 10.1111/pbi.12446
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Dε enhances Braasca napus growth and seed production in response to nitrogen availability

Abstract: SummaryPhospholipase D (PLD), which hydrolyses phospholipids to produce phosphatidic acid, has been implicated in plant response to macronutrient availability in Arabidopsis. This study investigated the effect of increased PLDe expression on nitrogen utilization in Brassica napus to explore the application of PLDe manipulation to crop improvement. In addition, changes in membrane lipid species in response to nitrogen availability were determined in the oil seed crop. Multiple PLDe over expression (PLDe-OE) lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The lipids were extracted from individual seed tissues and methyl‐esterified as described by Lu et al . (). Finally, 1 μl FA methyl ester solutions were injected into the GC‐MS.…”
Section: Methodsmentioning
confidence: 97%
“…The lipids were extracted from individual seed tissues and methyl‐esterified as described by Lu et al . (). Finally, 1 μl FA methyl ester solutions were injected into the GC‐MS.…”
Section: Methodsmentioning
confidence: 97%
“…An increasing number of studies have indicated that PLD, which is considered an important signaling enzyme in various organisms and is widespread in plants (Jang et al, 2012), participates in diverse physiological processes, such as development (Lu et al, 2016); hormone signaling mediated by abscisic acid (Peters et al, 2010), salicylic acid (Janda et al, 2015), jasmonic acid (Zhao et al, 2013), and auxin (Li and Xue, 2007); reactive oxygen generation (Wu et al, 2010); and in the response to abiotic and biotic stresses such as drought (Lu et al, 2012), high salinity (Yu et al, 2010), low temperature (Kargiotidou et al, 2010), and fungal infection (Liu et al, 2013). The diverse cellular functions of PLD suggest that the enzyme is subjected to complex regulation in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in lipids lead to the alterations of the fluidity (Dawaliby et al, ; Nguyen, Rudge, Zhang, & Wakelam, ), permeability (Colombini, ; Van der Paal, Neyts, Verlackt, & Bogaerts, ), and polarity (Hammond & Hong, ; Tejos et al, ) of the cell membrane. In plants, these alterations trigger cell response to environmental stimuli such as drought, salt, cold, nutrition, and pathogen (Hong et al, ; Lu et al, ; Peppino Margutti, Reyna, Meringer, Racagni, & Villasuso, ; Ruelland et al, ; Singh, Bhatnagar, Pandey, & Pandey, ). In plants, glycerolipids consist of monogalactosyldiacylglycerol (MGDG), digalactosyldiacylglycerol (DGDG), triacylglycerol (TAG), diacylglycerol (DAG), and different types of phospholipids (Wei, Fanella, Guo, & Wang, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to operate, and data analysis is simple. Previously, glycerolipids have not been comprehensively analyzed in seeds during different development stages of rapeseed (Katavic, Agrawal, Hajduch, Harris, & Thelen, ; Lu et al, ; Tang et al, ; Woodfield et al, ). We thus employed this approach to comprehensively analyze the glycerolipids from crude lipid extracts of rapeseed tissues in order to facilitate the understanding and study of lipid metabolism in rapeseed.…”
Section: Introductionmentioning
confidence: 99%